in vitro evaluation of marginal leakage using invasive and noninvasive technique of light cure glass ionomer and flowable polyacid modified composite resin used as pit and fissure sealant - Anshu Singla; Shalini Garg; Sanjeev Kumar Jindal; H P Suma Sogi; Deepak Sharma (Wolters Kluwer Medknow Publications, 2011)
Aim: This study compared the microleakage of light cure glass ionomer and flowable compomer as pit and fissure sealant, with and without tooth preparation. Materials and Methods: One hundred premolars that were extracted for orthodontic purpose were used. After adequate storage and surface debridement, the teeth were randomly divided into four groups. In Group I and III, the occlusal surfaces were left intact, while in Group II and Group IV, tooth surfaces were prepared. Teeth in Group I and Group II were sealed with Light cure glass ionomer, whereas flowable compomer was used to seal teeth in Group III and IV. The sealed teeth were then immersed in dye. Subsequently, buccolingual sections were made and each section was examined under stereomicroscope for microleakage followed by scoring. Results: In group I, microleakage score ranged from 2 to 4 with mean of 3.64 (±0.757), while in group II the range was observed to be 1-4 with mean of 2.88 (±1.236). Group III recorded a range of 0-4 with the mean of 2.20 (±1.443) while 0-2 and 0.60 (±0.707) being the range and mean observed, respectively, for group IV. Conclusion: Flowable compomer placed after tooth preparation showed better penetration and less marginal leakage than the light cure glass ionomer.